Noninvasive Techniques for Blood Pressure Measurement Are Not a Reliable Alternative to Direct Measurement: A Randomized Crossover Trial in ICU - Sara Ribezzo; Eleonora Spina; Stefano Di Bartolomeo; Gianfranco Sanson (The Scientific World Journal)
Introduction. Noninvasive blood pressure (NIBP) monitoring methods are widely used in critically ill patients despite poor evidence of their accuracy. The erroneous interpretations of blood pressure (BP) may lead to clinical errors. Objectives. To test the accuracy and reliability of aneroid (ABP) and oscillometric (OBP) devices compared to the invasive BP (IBP) monitoring in an ICU population. Materials and Methods. Fifty adult patients (200 comparisons) were included in a randomized crossover trial. BP was recorded simultaneously by IBP and either by ABP or by OBP, taking IBP as gold standard. Results. Compared with ABP, IBP systolic values were significantly higher (mean difference ± standard deviation 9.74±13.8; P<0.0001). Both diastolic (-5.13±7.1; P<0.0001) and mean (-2.14±7.1; P=0.0033) IBP were instead lower. Compared with OBP, systolic (10.80±14.9; P<0.0001) and mean (5.36±7.1; P<0.0001) IBP were higher, while diastolic IBP (-3.62±6.0; P<0.0001) was lower. Bland-Altman plots showed wide limits of agreement in both NIBP-IBP comparisons. Conclusions. BP measurements with different devices produced significantly different results. Since in critically ill patients the importance of BP readings is often crucial, noninvasive techniques cannot be regarded as reliable alternatives to direct measurements.